COMPUTATIONAL DESIGN OF NOVEL ORAL INSULIN CONJUGATES FOR THE DEVELOPMENT OF SOLID ORAL INSULIN DOSAGE FORMS - REDDY, JAYARAMA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Insulin is used to manage diabetes mellitus by subcutaneous injections regulary, that has become a part of patients life and is distressing for patients. Hence, we anticipate to get rid of the usage of subcutaneous injections completely from the medicine world and would make the diabetic people to say as “farewell to painful injections.” Methods: Virtual screening method (for selection of carriers), Toxtree tool (for toxicity evaluation of carriers), and discovery studio tool (for pharmacophore designing, absorption, distribution, metabolism, excretion, and toxicity [ADMET] analysis, designing oral insulin conjugates (OICs), and interaction studies between insulin receptor and OICs) were used for proposed study. Results: We have screened 14 competent drug delivering molecules (DDMs) from seven chemical compound databases. The ADMET and pharmacophoric properties of DDMs were analyzed by drug-informatics’ tools. Consequently, the DDMs were mono, di, and poly conjugated by covalent bonding with various binding sites of monomeric and hexameric form of human insulin and insulin-lispro (Humalog®) individually; and novel OICs were generated. Its binding efficiency and biological activity with insulin-receptor were determined. Conclusion: Inulin and Vitamin-B1 are the novel, safe, and proficient carriers for oral delivery of insulin. Insulin lispro is the remarkable option for oral delivery than other insulin forms.